2022
DOI: 10.1111/jhn.13017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of carbohydrate counting versus other forms of dietary advice in patients with type 1 diabetes mellitus: a systematic review and meta‐analysis of randomised clinical trials

Abstract: Background and aims Diabetes mellitus (DM) is one of the most prevalent chronic noncommunicable diseases globally, and the only way to reduce its complications is good glycaemic control. Insulin remains the only approved treatment for type 1 DM (T1DM) and is used by many with type 2 DM (T2DM). Carbohydrate counting is considered the ideal way to calculate meal‐related insulin doses as it allows greater flexibility in diet and could, in some people, reduce the burden of the disease. The primary objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“… 8 A meta-analysis of randomised controlled trials showed evidence favouring the use of the CC method and a significant reduction in HbA1c levels compared with that of controls. 13 However, CC is a complex skill that is subject to error among children and young adults with T1DM and their families. 16 Therefore, identifying opportunities to develop CC skills can improve interventions and achieve accurate CC by patients and improved glycaemic management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 A meta-analysis of randomised controlled trials showed evidence favouring the use of the CC method and a significant reduction in HbA1c levels compared with that of controls. 13 However, CC is a complex skill that is subject to error among children and young adults with T1DM and their families. 16 Therefore, identifying opportunities to develop CC skills can improve interventions and achieve accurate CC by patients and improved glycaemic management.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the efficacy and safety of the CC method in patients with T1DM 8 13–15. Scavone et al reported a significant reduction in glycated haemoglobin (HbA1c) levels, fewer hypoglycaemic events and decreased rapid insulin analogue doses after participants were taught about CC 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the focus is solely on carbohydrates and portions are not limited, patients may eat too many calories and overlook the amount and type of fats they consume 12. However, a recent systematic review and meta-analysis of randomized clinical trials indicated that carbohydrate counting does not relate to any substantial change in blood lipids or body weight 38. Nevertheless, weight change and lipid levels should be monitored and, when indicated, nutrition education and support provided to encourage eating patterns that align with the US Department of Agriculture's 2020-2025 Dietary Guidelines for Americans and the patient's weight goals 39…”
Section: Two Steps Of Advanced Carbohydrate Countingmentioning
confidence: 99%
“…As well, carbohydrate counting was not associated with an increased risk of hypoglycemia, blood lipid concentration, or weight changes. Besides, it seems to improve quality of life, specifically in the disease or its treatment domains, and despite being an iterative educational technique, its effectiveness is not affected by its use for up to two years (18).…”
Section: Introductionmentioning
confidence: 99%